PENGARUH ETOS KERJA DAN MANAJEMEN TALENTA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA UPTD KPHL SOLOK DINAS KEHUTANAN PROVINSI SUMATERA BARAT - Rinaldi; Almasdi (Media Mahardhika, 2024)
This study investigates the influence of work ethic and talent management on employee performance at the Solok Protected Forest Management Unit (KPHL) UPTD, with job satisfaction serving as a mediating factor. The research addresses issues of discipline among employees, as tardiness has negatively affected performance. This quantitative study surveyed the entire population of UPTD KPHL Solok employees, comprising 32 respondents, selected through total sampling. Data were collected via a Likert-scale questionnaire and analyzed using Smart PLS. The results show that both work ethic and talent management have a positive and significant effect on job satisfaction. Furthermore, while both factors positively affect employee performance, the impact is moderately significant. Job satisfaction plays a crucial mediating role, as employees perform better when they are satisfied with their jobs. Ultimately, the study concludes that work ethic and talent management significantly enhance employee performance through the mediating role of job satisfaction